Determinants of bond market development in Malaysia / Farissa Alyna Abdul Malek - Abdul Malek, Farissa Alyna (Faculty of Business and Management, 2018)
This study is on determinants of bond market development in Malaysia. It analyses the relationship between the economic size (GDP), trade openness (O), interest rate volatility (INTVOL), exchange rate variability (FXVOL), and size of banking system (BC). This study covers about the bond market development and is focused on what are the determinants that contributes to the bond market development. This study has chosen Malaysia to be focused on and the data is taken quarterly from the year 2008 to 2017. 40 observations were used in this study. Both single linear regression and multiple linear regression were used in this study to see the relationship between the independent variables and dependent variable. The problem that is pointed out in this study is regarding the foreign holdings which is worrying as it fell tremendously in late 2016 and started to fluctuate ever since. From this study, it is found that trade openness (O), exchange rate variability (FXVOL), and size of banking system (BC) has a significant relationship with bond market development (Y) while economic size (GDP) and interest rate volatility (INTVOL) has an insignificant relationship with bond market development (Y).